KREATIVITAS DALAM SENI FOTOGRAFI - Herlina, Yekti (Nirmana, 2003)
The art of photography is combination between technology and art. Esthetic values which not coveret in photography technology must be harmonized with technical process to give character and beauty at its visual result. The art of photography is not only simple record from the real world%2C but become the complex creation of art and the image medium that also give meaning and message. Abstract in Bahasa Indonesia : Seni fotografi adalah perpaduan antara teknologi dan seni. Berbagai nilai estetika yang tidak tercakup dalam teknologi fotografi harus diselaraskan dengan proses teknis untuk memberikan karakter dan keindahan pada hasil visualnya. Seni fotografi bukan sekedar merupakan rekaman apa adanya dari dunia nyata%2C tapi menjadi karya seni yang kompleks dan media gambar yang juga memberi makna dan pesan. art%2C photography%2C creativity.